A consecrated Virgin Wishes to Make Vows of Poverty and Obedience to the Bishop: Canon 604 - Bartone, Carlotta (Roman replies and CLSA advisory opinions 1996, 1996)
A sister in temporary profession in a contemplative order was refused permission to make perpetual vows. At the time of her departure from the monastery, she requested that the diocesan bishop receive her as a consecrated virgin. The bishop agreed, and the sister was received according to the Rite for the Consecration of Virgins. When she left the monastery, the former sister moved to a different diocese at a considerable distance. She later wrote to the bishop who had consecrated her and asked him to receive her vows of poverty and obedience, so that she might attain her spiritual desire for the “fullness” of religious consecration. She also stated her desire eventually to establish a contemplative monastery in Eastern Europe. What should the bishop respond?